(3bjGS CKQ GdGbJUGO GdQbej hJSYjQ GdCUhd ZjQ GdedehSI Ydi GdhYGA GdVQjHj ddTQcGJ PGJ GdfTGW GdOhdj (B: s (3OQGSI YedjI (B/s - (3,SGQg YHOGdaJGM eMehO eMeOs; (3YHOGdYRjR GdSjO eUWajs; (3YGOd MSjf KGHJs (2024)
(3JeKd GdgOa GdQFjSj ddHMK aj bjGS CKQ GdGbJUGO GdQbej hJSYjQ GdCUhd ZjQ GdedehSI Ydi GdhYGA GdVQjHj ddTQcGJ PGJ GdfTGW GdOhdj, hGYJeGOG Ydj GdHjGfGJ GdChdjI GdeLeYI ef NdGd bhGFe GdGSJHjGf (B((3GdGSJbUGA(B) (3GdehRYI Ydj cdkG ef GdeOjQjf hGdeQGLYjf HhMOI GdJLGQI GdEdcJQhfjI HeUdMI GdVQGFH GdeUQjI, hGdeOjQjf hGdeQGLYjf HEOGQI JSYjQ GdeYGedGJ hGdGJaGbjGJ GdOhdjI HeUdMI GdVQGFH GdeUQjI, GdeOjQjf GdeGdjjf hGdeQGLYjf heSDhdj JSYjQ GdeYGedGJ HecGJH GdeMGSHI GdcHQi (BBIG4(3, GdeOjQjf GdeGdjjf heQGLYjf GdVQGFH HGdTQcGJ PGJ GdfTGW GdOhdj GdJj JYed aj GdeLGd GdQbej, hGdHGMKjf hGdCcGOjejjf aj eLGd GdVQGFH GdOhdjI aj LeghQjI eUQ GdYQHjI, MjK bGeJ GdHGMKI HJaQjZ GdQOhO Ydi GdGSFdI HLOGhd GdHjGfGJ hJe JMdjdgG hGSJNdGU GdfJGFL ef NdGd JWHjb HYV GdGSGdjH GdGMUGFjI GdhGQOI HMReI GdHQGeL GdGMUGFjI ddYdhe GdGLJeGYjI (BStatistical Package for Social Science (3GdeYQhaI GNJUGQG HGSe (B(SPSS) (3hbO GSJYGfJ GdHGMKI GjVG HHQfGeL (B(AMOS) (3HGdEVGaI Gdj eYGed GdaG cQhfHGN (BCronbach's alpha (3dbjGS KHGJ GdGSJHjGf, heYGed GdGJSGb GdOGNdj (BInternal consistency(3, hGdJMdjd GdYGedj GdJhcjOj (BConfirmatory factor analysis (3ef NdGd HQfGeL (BAmos(3, hGdEMUGAGJ GdhUajI (BDescribtive statistics (3ddHjGfGJ ef NdGd MSGH HYV GdebGjjS eKd GdhSW GdMSGHj (BMean (3hGdGfMQGa GdeYjGQj (BStandard Deviation (3hGdNWC GdeYjGQj (BStandard Error (3hPdc dJMOjO SeGJ GJLGgGJ GSJLGHGJ eaQOGJ GdYjfI, hGNJHGQ (BT-Test(3dGNJHGQ JSGhi eJhSW cd YHGQI eY GdhSW GdGaJQGVj (B(3) (3eMGjO hcPdc dGNJHGQ eYfhjI eYGedGJ GdGfMOGQ, hGNJHGQ aQjOeGf (BFriedman Test (3dbjGS GdGgejI GdfSHjI dYHGQGJ GHYGO GdOGQSI, hfehPL GdGfMOGQ GdNWi GdHSjW (BSimple Linear Regression Model(3, hefgLjI fehPL GdeYGOdGJ GdgjcdjI Ch GdHfGFjI (BStructural Equation Model (SEM)(3, hGNJHGQ eGf hjJfi (BMann-Whitney Test (3dJMdjd GdJHGjf HGdfSHI ddeLehYGJ GdKfGFjI, hGNJHGQ cQhScGd hGdGS (BKruskal-Wallis (3dJMdjd GdJHGjf HGdfSHI ddeLehYGJ GdGcKQ ef aFJjf, hbO CXgQJ fJGFL GdJMdjd GdEMUGFj hLhO YdGbI EjLGHjI heYfhjI Hjf GdGbJUGO GdQbej hGdhYGA GdVQjHj ddTQcGJ PGJ GdfTGW GdOhdj hcPdc hLhO YdGbI EjLGHjI heYfhjI Hjf JSYjQ GdCUhd ZjQ GdedehSI hGdhYGA GdVQjHj ddTQcGJ PGJ GdfTGW GdOhdj(B.s
The main objective of this research is to measure the impact of the digital economy and the pricing of intangible assets on the tax base of companies engaged in international activities. This study relies on primary data collected through questionnaires distributed to managers and auditors at the e-commerce unit of the Egyptian Tax Authority, managers and auditors in the Transactions Pricing and International Agreements department of the Egyptian Tax Authority, financial managers, auditors, and Transfer pricing officers at major BIG4 accounting firms, financial managers and tax auditors at international digital companies operating in Egypt, as well as researchers and academics in the field of international taxation in the Arab Republic of Egypt. The researcher transcribed the questionnaire responses into data tables, analyzed them, and extracted the results using various statistical methods provided by the Statistical Package for Social Science (SPSS) and the AMOS software. The researcher also utilized Cronbach's alpha coefficient to measure questionnaire reliability, internal consistency, and Confirmatory Factor Analysis through the Amos software. Descriptive statistics were computed to determine features of response trends, including mean, standard deviation, and standard error. These statistics were used to test the neutrality of responses using the T-Test and to test the significance of regression relationships. Furthermore, Friedman Test was employed to measure the relative importance of study dimension phrases, and both the Simple Linear Regression Model and Structural Equation Model (SEM) were used. Mann-Whitney Test was applied to analyze variance between binary groups, while Kruskal-Wallis Test was used to analyze variance between groups with more than two categories. The statistical analysis revealed a significant and positive relationship between the digital economy and the tax base of internationally active companies, as well as a significant and positive relationship between the pricing of intangible assets and the tax base of such companies.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B181-190.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdTQcGJ GdOhdjIs; (3GdVQGFHs -- (3eMGSHIs; (3GdGbJUGO GdQbeis; (3GdGbJUGO GdQbejs -- (3GdJLGQI GdEdcJQhfjIs -- (3JSYjQ GdeYGedGJs